Dampak Penggunaan Quantum Teaching Terhadap Pembelajaran Pada Mata Pelajaran IPS - Pandu cahya Widihartanto; Sujarwo Sujarwo (FKIP, Universitas Palangka Raya, 2023)
Education is one of the most important parts in an effort to advance the life of the nation. Because of the need for special attention in the use of learning models to support the course of learning. Quantum teaching is one of the suitable learning models to be applied to the course of learning. In this article, we will discuss the impact given by the use of quantum teaching on social studies subjects in junior high schools. Writing articles using the article review method by presenting the contents of various previous studies to find out how the impact given by the use of quantum teaching is. Quantum teaching has a positive impact on the learning system that affects several things. starting from learning outcomes, how students can be motivated to learn, and also the emergence of various kinds of potential that are given to the implementation of more interesting learning styles to be given to students